2022
DOI: 10.1001/jamaoncol.2021.5680
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Mediated Diseases Associated With Cancer Risks

Abstract: Key Points Question What are the profiles of cancer risk associated with immune-mediated diseases? Findings In this cohort study of 478 753 participants, immune-mediated diseases were associated with an increased risk of total cancer. Organ-specific immune-mediated diseases had stronger associations with risk of local cancers than extralocal cancers, and many immune-mediated diseases were associated with increased risk of cancer in the involved organs and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 70 publications
(101 reference statements)
2
55
0
6
Order By: Relevance
“…In addition, a number of studies have demonstrated that SLE is associated with an increased incidence of malignancies, particularly NHL, with an estimated four-to sevenfold increased risk of NHL in patients with SLE than in the general population. 25,26 These results indicated that the alterations in these proteins represented a major biological feature of the blood environment of AIDS-NHL. We found that, among the top 10 high-degree core DEPs identified from the PPI network, half of the proteins were involved in the complement and coagulation cascade pathway, which included the CFH, C1QA, C1QC, C1QB, and CFHR1 proteins.…”
Section: Biomarker/dep Validation In Hiv-infected Patients With or Wi...mentioning
confidence: 79%
“…In addition, a number of studies have demonstrated that SLE is associated with an increased incidence of malignancies, particularly NHL, with an estimated four-to sevenfold increased risk of NHL in patients with SLE than in the general population. 25,26 These results indicated that the alterations in these proteins represented a major biological feature of the blood environment of AIDS-NHL. We found that, among the top 10 high-degree core DEPs identified from the PPI network, half of the proteins were involved in the complement and coagulation cascade pathway, which included the CFH, C1QA, C1QC, C1QB, and CFHR1 proteins.…”
Section: Biomarker/dep Validation In Hiv-infected Patients With or Wi...mentioning
confidence: 79%
“…Evermore accurate and expanding archiving of clinical and biological patient data greatly facilitates the discovery of novel epidemiological associations among different diseases. A recent study published in JAMA Oncology 1 exploits a large dataset involving 478 753 participants to investigate the relationship between cancers and “immune-mediated diseases”, which is a heterogeneous collection of pathological conditions. Such diseases may be either organ-specific or systemic, involve a mostly inflammatory process without the recognition of specific autoantigens (as this may apply to Crohn’s disease, psoriasis, sarcoidosis and ulcerative colitis), an overreaction to exogenous allergens (as this is the case in allergic rhinitis, asthma and celiac disease) or the unwarranted recognition of specific autoantigens with a variable contribution of autoreactive T lymphocytes and autoantibodies.…”
mentioning
confidence: 99%
“…However, the study in JAMA Oncology has sufficient power to unveil more subtle associations between specific immunologically relevant diseases and distinct categories of malignancy that can be either positive or negative. 1 …”
mentioning
confidence: 99%
See 2 more Smart Citations